Serum Adipokine Levels as a Predictor of Liver Damage in Patients with Metabolic-Associated Fatty Liver Disease Pathogenetic Mechanisms of Acute Coronary Syndrome (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Until recently, most authors believed that pathological changes in liver damage in patients with metabolic-associated fatty liver disease. Insulin resistance (IR) is considered one of the important mechanisms involved in the pathogenesis of metabolic liver dysfunction. It is widely known that the development of steatosis is associated with the accumulation of fat in the liver and insulin resistance (IR), and IR is considered to be the main pathogenetic cause of liver steatosis. It is widely recognized that the development of steatosis is associated with hepatic fat accumulation and insulin resistance (IR), with IR believed to be the main pathogenetic cause of hepatic steatosis.